Automatic vehicle collision avoidance system - Islam, Ashikul; Oyshi, Sohana Salim; Sohan, Faisal Mahmud; Usama, Syed Ahmed (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.